Maternal health literacy plays a greater role than paternal health literacy in adolescent physical activity in China: a cross-sectional study - Yu, Nanfang (Frontiers in Public Health, 2025)
BackgroundGiven the prevalence of obesity and physical inactivity among Chinese adolescents, assessing the role of parents in this situation is important. Therefore, the main aim of this study was to evaluate the association between parental health literacy levels and adolescents' physical activity and obesity in China.MethodsIn this cross-sectional study, a sample of 4,717 Chinese high school students and their parents participated. Parental health literacy was measured using the Chinese version of the Health Literacy Survey 2019-12-item questionnaire (HLS19-Q12), and adolescents' physical activity was assessed using the short version of the International Physical Activity Questionnaire (IPAQ). Body mass index (BMI) was calculated using standardized measurements of weight and height (kg/m2). Statistical analyses, including independent t-test and multiple linear regression (to examine predictors of adolescent physical activity and BMI) were performed using SPSS 26.0 software. The significance level was set at p < 0.05.ResultsA total of 31.95% of adolescents were overweight or obese, and 48.15% had low physical activity, which was significantly lower in girls than in boys (p = 0.01, Cohen's d = 0.212). Only 21.39% of parents had excellent health literacy. Higher maternal health literacy was significantly associated with increased physical activity in boys, whereas both maternal and paternal health literacy were associated with higher physical activity in girls, with maternal health literacy showing a stronger association than paternal health literacy (p < 0.001). Furthermore, low physical activity was the only factor significantly associated with higher BMI among students (p < 0.001).ConclusionThe findings highlight the importance of addressing the health literacy of parents, especially mothers, in promoting adolescent physical activity and preventing obesity. Health promotion programs and educational policies should consider family-based approaches to effectively address gender-specific needs and improve adolescent health outcomes.